THE TRANSFORMATION OF PSYCHOPHYSIOLOGICAL FUNCTIONS OF MILITARY PILOTS WITH DIFFERENT PROFESSIONAL QUALIFICATION AND AGE - Kalnysh, V.V.; Shepitko, K.V.; Trinka, I.S.; Kravchuk, V.V.; Pashkovsky, S.M. (World of Medicine and Biology, 2021)
The paper presents the results of the investigations related to revealing the transformation peculiarities of a complex of psychophysiological functions of military pilots of supersonic, subsonic, transport and helicopter aviation with due respect to their qualification level and age. The authors outline the descriptive list of psychophysiological characteristics that change regularly because of improving professional competence. They also specify the regular decrease in the level of significance of the correlation relationship between qualification and a complex of psychophysiological functions in pilots of supersonic, subsonic and transport aviation. As far as helicopter pilots are concerned, the increase in the body compensatory abilities under carrying out less intensive work results in the natural increase in such relationships. Moreover, the availability of trustworthy correlation relationships between the qualification of pilots and their age is shown. Furthermore, this relationship in supersonic aviation pilots is manifested much stronger than in other categories.